Prevalence of Intestinal Parasite Infections and Associated Factors among Pregnant Women in Northwest Ethiopia - Yibeltal Aschale; Awoke Minwuyelet; Tadesse Yirga Akalu; Asmare Talie (Journal of Parasitology Research)
Background. Intestinal parasite infections are among the most common infections worldwide. They pose a high burden in pregnant women in developing countries causing maternal anemia, low birth weight, and prenatal mortality. This study is aimed at assessing intestinal parasite infection prevalence, species diversity, and associated factors among pregnant women. Methods. A community-based cross-sectional study was conducted among pregnant women in Debre Elias district from March 2021 to July 2021. Three hundred sixty-three study participants meeting the inclusion criteria were enrolled for the study, and all submitted the required amount and quality of stool specimen. Immediately after collection, macroscopic (gross) and microscopic (saline wet mount) examination of stool sample was performed to detect and identify intestinal parasites. The generated data were checked for completeness, coded, entered, and analyzed using SPSS version 20.0 (SPSS Inc., Chicago, 2011) software. Binary logistic regression was applied to show significant association between dependent and independent variables. Statistically significant association was declared at a P value of < 0.05. Result. Of the study participants screened for intestinal parasite, 43.5% (158/363) were infected with at least one intestinal parasite. From the total positives, 40.5% (147/363) were mono and 3.0% (11/363) were double infections. Five intestinal parasite species were recorded, of which hookworm was the predominant, (65.2%, 103/158) followed by E. histolytica/dispar (12.7%, 20/158) and G. lamblia (11.4%, 18/158). Ascaris lumbricoides and Taenia species comprised the least percentage (1.9%, 3/158 each). Source of drinking water and occupation were identified as significant factors associated with intestinal parasite infection. Farmer pregnant women were 6.41 times (AOR=6.41, 95% CI: 1.05-39.16; P=0.034) more likely to be infected by intestinal parasites than their counterparts. Pregnant women who drank tape water were 0.52 times less (AOR=0.52, 95% CI: 0.30-0.88; P=0.017) likely to be infected by intestinal parasites. Conclusion. Intestinal parasite infections remained a serious health burden to pregnant women in the study area with the dominance of a hematophagous worm (hookworm). Community-based intestinal parasite screening and treatment are essential to alleviate the burden caused by intestinal parasite infections.